The Difference in Achievement Motivation between Students with Learning Disability and Without Learning Disability - Jilsy P; Dr Mansi Kapoor (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Achievement motivation is an important psychological construct that influences student’s academic behaviour, perseverance, and overall learning outcomes. The present study aims to examine the difference in achievement motivation between students with learning disabilities (LD) and students without LD. The sample consisted of 300 participants, including 150 students with LD and 150 students without LD, all within the age range of 8–12 years. Ray’s Achievement Motivation Scale was administered to assess levels of goal orientation, task persistence, and aspiration among the participants. A purposive sampling technique was adopted for sample selection. The study was guided by the hypothesis that students with LD would exhibit higher achievement motivation, whereas students without LD would show comparatively lower achievement motivation. To analyze the difference between the two groups, an independent sample t-test was employed. The results did not support the hypothesis, as there was no significant difference in achievement motivation between students with learning disabilities and those without learning disabilities. Although the mean score of students with learning disabilities was slightly higher, this difference was not statistically meaningful. These findings indicate that the presence of a learning disability does not necessarily reduce a student's drive to succeed. Instead, children with learning disabilities may maintain comparable levels of motivation through resilience, supportive learning environments, and adaptive coping strategies.
Keywords: Achievement motivation; Learning Disability